P050 Improving management and partner notification outcomes of women treated for pelvic inflammatory disease (PID) by innovative yet simple bespoke measures. (30th June 2016) - Connolly, Noel B; Stott, Cheryl; Ward, Mike; McQuillan, Orla
Abstract : Background: PID is a common condition seen at genitourinary clinics. BASHH published NICE approved guidelines in 2011. To improve consistency amongst clinicians we designed a simple aide memoire tick-box sticker. To improve health adviser (HA) contact and reduce "did-not-attend" (DNA) rates we established a HA staffed telephone follow-up clinic Methods: We regularly audit both management of PID and follow-up and so were able to compare data (2011–2015) to demonstrate improvements in practice with these changes Outcome: Partner notification rates improved from 50% to 67% helped mainly by the telephone clinic as HA documented in all cases whether partners had been screened/treated. 82% had a recording of symptom change, previously 77%. For those followed-up using the telephone clinic proforma this was 100%. Results for the number of named male contacts screened for infection and/or treated have improved (2011 = 0.21; 2014 = 0.38; 2015 = 0.48) and we now achieve above the BASHH target (0.4 – large city centre clinic). Over the past five years introducing these measures into clinic has improved all outcomes except DNA rate which remains stubborn (33% vs 27%). For a large city centre clinic the reasons behind this are complex and varied Conclusions: Innovative yet simple measures can be easily introduced which have a positive impact on guideline adherence and also make audit an easier task. With the advent of EPR in many clinics these initiatives should be transferable and aid standardising management across the GU network particularly during this time of change and service integration